DEIKSIS PERSONA BAHASA SUNDA DALAM FILM GAMPANG CUAN KARYA RAHABI MANDRA: KAJIAN PRAGMATIK - Iglima Dahlia Mutiara; Hera Meganova Lyra; Asri Soraya Afsari (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
The research aims to describe the types of person deixis and the social age relations that can influence the choice of person deixis. This research is motivated by the importance of understanding the use of the Sundanese language in accordance with the speech context. This study utilizes a pragmatic approach based on Yule's theory (2014) to understand age and situational contexts, while the classification of person deixis types employs Purwo's theory (1984). The method used is a descriptive qualitative method with listening and note-taking techniques, followed by data analysis using the referential identity method, whereas the presentation of results uses an informal method. Sundanese utterances in the film Gampang Cuan serve as the data source in investigating person deixis. The film Gampang Cuan contains the use of person deixis across a varying age range, resulting in diverse person deixis data. The research results indicate 91 person deixis data, consisting of 31 data of first-person singular deixis (the forms urang and aing), 2 data of first-person plural deixis (the form urang), 50 data of second-person singular deixis (the forms manéh, sia, and the suffix -na), 1 datum of second-person plural deixis (the form maranéh), 6 data of third-person singular deixis (the form manéhna), and 1 datum of third-person plural deixis (the suffix form -na). An interesting fact within it through the analysis of social age relations (old-young, young-old, peers) proves that the age of the speaker and the addressee/third party influences the choice of person deixis types, with the most dominant form found being the second-person singular deixis and the young-old social age relation.